The Efficiency of Utilizing The Physioex® Application Through E-Learning Among Students in The Field of Health at Universitas Negeri Gorontalo - Puluhulawa, Tesya Gamananda; Pateda, Sri Manovita; Abbas, Jeane Novita Irene; Paramata, Nanang Roswita; Irmawati, Irmawati (Jambura Medical and Health Science Journal, 2024)
Introduction: Physiology is a study of the normal functions of the human body. However, the traditional lecture-based approach to teaching this subject has been observed to cause disengagement and boredom among students. Universitas Negeri Gorontalo was exploring the use of PhysioEx®, an interactive e-learning laboratory to studying physiology. This study aims to identify effective teaching methods to enhance student learning outcomes in physiology courses.Method: A true experimental study was carried out at the Faculty of Medicine in Universitas Negeri Gorontalo in October 2023 with a pretest and posttest group. Each test comprised of nine questions and had a time limit of nine minutes. The study population consisted of 200 Public Health students and 69 medical students from the year 2023. A sample of 161 random individuals was selected for analysis using the Slovin formula, and the data was analyzed using the T-test analysis.Results: Based on the statistical analysis of the pretest and posttest scores, it was observed that both the lecture method and the PhysioEx® method resulted in a significant increase in scores (p0.05). However, no substantial difference was observed in the learning outcomes between the two methods (p 0.05).Conclusion: The comparative effectiveness of the lecture method and the PhysioEx® method in the instruction of physiology has been analyzed. The findings indicate that both methods are similarly effective when employed in educational contexts pertaining to physiology. The results of this analysis underscore the utility and potential of both pedagogical approaches. Keywords: Learning effectiveness, e-learning, physiology, physioEx®